2018
DOI: 10.1007/s10552-018-1042-z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing preoperative body size in breast cancer patients between 2002 and 2016: implications for prognosis

Abstract: Overweight and obesity are increasing worldwide, but the extent in breast cancer patients is unknown. The two aims were to study secular trends in preoperative body mass index (BMI), waist circumference, and breast volume and their impacts on clinical outcome. BMI, waist circumference, and breast volume were measured preoperatively in 24–99-year-old primary breast cancer patients (n = 640) in Sweden 2002–2016. The measurements were analyzed alone and combined in relation to recurrence and overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…A recent study based on the BCBlood cohort showed that a breast volume ≥850 ml was the strongest prognostic anthropometric factor in terms of breast cancer-free interval, both in all patients and in various treatment groups. Meanwhile, BMI and waist circumference were the strongest prognostic anthropometric factors for overall survival ( 38 ). Given the inverse association between the body size and the IGF-I/IGFBP3 molar ratio, it is unlikely that the association between breast volume and recurrence-risk is mediated via increases in IGF-I or IGFBP-3.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study based on the BCBlood cohort showed that a breast volume ≥850 ml was the strongest prognostic anthropometric factor in terms of breast cancer-free interval, both in all patients and in various treatment groups. Meanwhile, BMI and waist circumference were the strongest prognostic anthropometric factors for overall survival ( 38 ). Given the inverse association between the body size and the IGF-I/IGFBP3 molar ratio, it is unlikely that the association between breast volume and recurrence-risk is mediated via increases in IGF-I or IGFBP-3.…”
Section: Discussionmentioning
confidence: 99%
“…Primary breast cancer patients assessed preoperatively since October 2002 at the Skåne University Hospital in Lund were asked to join a prospective cohort study regarding lifestyle factors, as previously described [5]. The preoperative visit typically took place a few weeks after diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrently, an obesity epidemic has emerged worldwide, which negatively impacts both breast cancer risk and recurrence [3,4]. Preoperative body sizes increased significantly 2002-2016 with a negative prognostic impact [5]. Weight change has been investigated in multiple studies, but the impact on breast cancer prognosis remains unclear [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…First, current evidence shows that a larger body size, which is usually indicated by a higher BSA or BMI, may predispose to LNM and further require extensive lymph node dissection in a variety of oncological specialties, resulting in a poor prognosis. [33][34][35][36][37] In our cohort, both N1 and N2 stage LNM were more frequently observed in patients with BSA > 1.69 m 2 than in patients with BSA ≤ 1.69 m 2 , although LNM is not associated with a risk of chylothorax (Table 1). Mediastinal lymph nodes are generally located around important blood vessels and airways.…”
Section: Interpretationsmentioning
confidence: 97%